Perbaikan Sanitasi dan Higienis Kerupuk Kulit IKM Aulia di Kabupaten Agam, Provinsi Sumatera Barat - Indri Juliyarsi; Sri Melia; Deni Novia (Universitas Muhammadiyah Parepare)
Skin crackers from IKM Aulia in Agam Regency, are already well-known and popular as regional superior products that have great potential to be developed. The purpose of this service is to improve sanitation and hygiene aspects and to improve spatial planning in accordance with the provisions of the SSOP (Sanitation Standard Operating Procedures) and GMP (Good Manufacturing Practice). Approval methods are offered to support the discussion program's knowledge of training and consultation methods through lecture and discussion methods. The focus of activities is to renovate the production space and promote the improvement of sanitation and hygiene during production and sanitation equipment. Service is applied to applications and applications of appropriate technology. Mitra is very enthusiastic about increasing the area of tourism and hygienic production through the use of cleaning tools for wet and safe skin production rooms quickly and hygienically. Increased storage space for leather crackers is equipped with a container box so that the shelf life of the skin can be extended after drying, as well as an increase in production space, layout so that production can run well, meeting SSOP and GMP requirements in production.